Literature Review : LITERATUR REVIEW HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEAKTIFAN LANSIA DALAM MENGIKUTI POSYANDU LANSIA - Huda, Alfin Rulian; Roni, Faishol; Wijaya, Arif (LPPM STIKes Bahrul Ulum Jombang, 2023)
Aging is a natural process accompanied by a decrease in physical condition with a visible decrease in the function of the body's organs. The disobedience of the elderly in participating in the activities of the elderly Posyandu includes decreased physical abilities, decreased concentration power and family support to deliver or to remind the elderly to come to the elderly Posyandu. The purpose of the literature review is to determine the relationship between family support and the level of activeness of the elderly in participating in the elderly Posyandu. This article uses the literature review method using the Google Scholar database, Crossref.org, DOAJ. The journals taken for publication in 2017-2021 obtained 512 articles which were then excluded so that 10 articles were obtained. The results of this literature review were reviewed so that the fifteen articles had a relationship between family support and the level of activity of the elderly in participating in the elderly Posyandu. It is hoped that families will support the activity of the elderly in participating in activities at the elderly Posyandu.